PENGARUH PROFITABILITAS, LIKUIDITAS, OPERATING LEVERAGE DAN GROWTH OPPORTUNITY TERHADAP STRUKTUR MODAL - Carolina, Valentina; Santioso, Linda (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This study aims to analyz profitability, liquidity, operating leverage, and growth opportunity to the capital structure on manufacturing companies listed on Indonesia Stock Exchange sector primer consumption and non primer consumption during 2018-2021. The variables studied were ROA as an indicator of profitability, CR as an indicator of liquidity, DOL as in indicator of operating leverage, GO as an indicator of growth opportunity and DER as in indicator of capital structure. Sample was selected using purposive sampling method and the valid data was 49 companies by using Eviews version 10 and Miscrosoft Excel 2016 as the tool to analyz. The results of this study is protitablity, liquidity and operating leverage whereas no significant effect and growth opportunity significant effect on capital structure The implication of this study is need to maximum analyz growth opportunity in companies because ir can have a big impact on the future in company and provide many benefits for internal or oeksternal parties in company.